PENERAPAN STRATEGI PEMBELAJARAN 3M (MENIRU, MENGOLAH DAN MENGEMBANGKAN) UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI DAN PRESTASI BELAJAR SISWA - Lelariana (UNIB Press, 2022)
The purpose of this study (1) The application of 3M Learning Strategies can improve students' Poetry Writing Ability in Indonesian class VIII MTs Negeri 1 Pagar Alam subjects. (2) The application of 3M learning strategies can improve students' learning achievement in Indonesian class VIII subjects at MTs Negeri 1 Pagar Alam (3) The effectiveness of the application of 3M learning strategies when compared to conventional learning methods. The type of research used is Classroom Action Research (CAR) with 4 stages, namely 1. Action Planning, 2. Action Implementation, 3. Observation and 4. Reflection. This research was conducted in 3 cycles, namely Cycle 1, Cycle 2 and Cycle 3. The population in this study were students of class VIII MTs Negeri 1 Pagar Alam totaling 197 people. Sampling is done by total sampling, namely the sample is determined by making the entire population into a sample. The research sample that acts as an action class is class VIII.1 MTs Negeri1 Pagar Alam, totaling 28 students. Data collection techniques using observation sheets and tests. The results of this study are the application of 3M learning strategies can improve students' poetry writing skills and student achievement in class VIII MTs Negeri 1 Pagar Alam